Pengaruh Pendidikan dan Pelatihan terhadap Kinerja Pegawai Negeri Sipil (PNS) - Istiqomah Istiqomah; Syifi Fauziyah; Alifatul Husna (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study is to determine the effect of education and training on the performance of Civil Servants (PNS) at the Department of Industry, Trade and Cooperatives, Small and Medium Enterprises of Paser Regency. The research design used in this study is quantitative research. The population in this study were all Civil Servants (PNS) consisting of 31 people at the Department of Industry, Trade and Cooperatives, Small and Medium Enterprises of Paser Regency. The sampling technique in this study was saturated sampling, namely the entire population was used as a sample. The sample in this study was 31 people. The types of data in this study are qualitative data and quantitative data. The data sources used are secondary data and primary data. The data collection technique used in this study was by observation and distributing questionnaires. Data analysis in this study used multiple linear regression analysis with the help of SPSS version 25. The results of the study indicate that education (X1) obtained a t count of 0.227 with a significant level of 0.882 and when compared with the t table of 2.04841, then the t count < t table of 0.227 < 2.04841, which means that the education variable (X1) does not have a significant effect on the performance of Civil Servants (PNS) (Y) because H0 is accepted and Ha is rejected. For training (X2) obtained a t count of 6.038 with a significant level of 0.000 and when compared with the t table of 2.04841, then the t count > t table or 6.038 > 2.04841, which means that the training variable (X2) has a significant effect on the performance of Civil Servants (Y) because H0 is rejected and Ha is accepted.